Do children and adolescent ice hockey players with and without a history of concussion differ in robotic testing of sensory, motor and cognitive function?. Issue 1 (December 2016) - Little, C.; Emery, Carolyn; Scott, Stephen; Meeuwisse, Willem; Palacios-Derflingher, Luz; Dukelow, Sean
Abstract Background KINARM end point robotic testing on a range of tasks evaluating sensory, motor and cognitive function in children/adolescents with no neurologic impairment has been shown to be reliable. The objective of this study was to determine whether differences in baseline performance on multiple robotic tasks could be identified between pediatric/adolescent ice hockey players (age range 10–14) with and without a history of concussion. Methods Three hundred and eighty-five pediatric/adolescent ice hockey players (ages 10–14) completed robotic testing (94 with and 292 without a history of concussion). Five robotic tasks characterized sensorimotor and/or cognitive performance with assessment of reaching, position sense, bimanual motor function, visuospatial skills, attention and decision-making. Seventy-six performance parameters are reported across all tasks. Results There were no significant differences in performance demonstrated between children with a history of concussion [median number of days since last concussion: 480 (range 8–3330)] and those without across all five tasks. Performance by the children with no history of concussion was used to identify parameter reference ranges that spanned 95 % of the group. All 76 parameter means from the concussion group fell within the normative reference ranges. Conclusions There are no differences in sensorimotor and/or cognitive performance across multiple parameters using KINARM end point robotic testing in children/adolescents with or without a history of concussion.